Is Fibromyalgia Syndrome a Neuropathic Pain Syndrome? - Meryem KÖSEHASANOĞULLARI; Nihan ERDİNÇ GÜNDÜZ and Elif AKALIN (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate whether fibromyalgia syndrome (FMS) represents a neuropathic pain syndrome through the use of neuropathic pain scales. Patients and methods: The study included 99 female patients (mean age 44.21 years; range, 18 to 65 years) who referred to Physical Therapy and Rehabilitation Department Outpatient Clinics with complaints of widespread pain and who received a clinical diagnosis of fibromyalgia based on the 1990 American College of Rheumatology diagnostic criteria and a control group consisting of 86 female patients (mean age 49.21 years; range, 18 to 65 years) who were diagnosed with acute subacromial impingement as a nociceptive pain model. All patients completed the Turkish version of the Fibromyalgia Impact Questionnaire (FIQ), the Beck Depression Scale (BDS), the 10 cm Visual Analog Scale for pain assessment, the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) pain questionnaire for neuropathic pain assessment and the painDETECT scale. Results: An evaluation of the patients’ symptoms indicated that complaints of numbness, burning, tingling, morning stiffness, insomnia, fatigue and weakness were significantly more common in the fibromyalgia group compared to the controls. Moreover, the mean scores of the BDS, FIQ, painDETECT and LANSS pain scale were significantly higher in the fibromyalgia group compared to the controls. Statistically significant correlations were noted between FIQ values and LANSS, and the BDS and painDETECT results in the fibromyalgia group. Conclusion: The present study demonstrates that sensorial symptoms such as paraesthesia, hyperalgesia and allodynia were more common and the scores of neuropathic pain scales such as painDETECT and LANSS were significantly elevated in the fibromyalgia patients compared to the control group, and these findings suggest that FMS may have a neuropathic pain component.